PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE THE POWER OF TWO TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS VII SMP N 1 KEPENUHAN HULU - -, Fatmawati; Deswita, Hera; Richardo, Rino (Universitas Pasir Pengaraian, 2015)
The purpose of this research is to know whether is the effect of cooperative learning model The Power of Two typetowards result of studying mathematics student. The kind of this research is quasi experiment in which class appliedcooperative learning model The Power of Two on 7th grade class of SMP N 1 Kepenuhan Hulu and class control wasgiven conventional learning model. The technique taking sampling is sampling saturated technique. The Hypothesistesting used T-test. The result of calculation got tcount = 2,173 and ttable = 2,034. This show that tcount > ttable at 5% significane level.Thus there is the effect of cooperative learning model The Power of Two type toward result of studying mathematics student on 7th grade class of SMP N 1 Kepenuhan Hulu.